Development of Articulate Storyline 3-Based Media with the Problem-Based Learning Model in Pancasila Education for Fourth Grade Elementary School Students - Divia Rahmadini; Muhammadi (Journal of Practice Learning and Educational Development, 2025)
This research is motivated by the lack of ICT-based Pancasila education learning media in Elementary Schools. So teachers need to improve their ability to process ICT-based learning media so that students are motivated and actively involved in learning. Based on these problems, this study aims to develop learning media in the form of Articulate Storyline 3 media using the Problem Based Learning (PBL) model in Pancasila Education learning in grade IV of elementary schools that is valid, practical and effective. This research is a development research (R&D) with the ADDIE model. The ADDIE model consists of five steps, namely: analysis, design, development, implementation, and evaluation. The designed media is then validated by a validator using a validation sheet in the form of a questionnaire. Product validation consists of material experts, media experts and language experts. For product practicality, it is done by filling out a questionnaire of teacher responses and student responses. Then, for effectiveness, it is done by giving evaluation questions to students. The subject of the product trial was at SDN 04 Bukik Apik Puhun, Bukittinggi City and the subject of product research was at SDN 02 Percontohan, Bukittinggi City. The results of the study showed that the Articulate Storyline 3 media obtained a material validity of 77.5% (quite valid), language validity of 97.5% (very valid), and media validity of 87.5% (very valid). Based on the results of teacher responses and student responses at the trial school, it is known that learning using the Articulate Storyline 3 media is very practical with a percentage of practicality from teacher responses at the trial school of 92.5%, and a percentage of practicality from student responses of 90.5%. The percentage of teacher responses at the research school was 96.2% and the percentage of student responses was 89.6%. The results of the effectiveness of the learning media showed very effective results with a percentage reaching 89.2% with an effective category. Thus, it can be concluded that the Articulate Storyline 3 media with the Problem Based Learning model in grade IV of elementary school has been declared valid, practical and effective for use in learning.